ANALISIS DAMPAK PENGUMUMAN DEVIDEN TERHADAP REAKSI PASAR (Study Pada Perusahaan Indeks LQ 45) - Sari, Syara Purnama; Lestari, Winda Rika (Jurnal Manajemen Magister Darmajaya, 2015)
The purpose of this research was to analyze market reaction on cash dividends announcement at LQ45 Index company in the year of 2014. The sample in this research was 22 companies, taken by purposive sampling technique with event study method. The data analysis method for hypothesis test used paired sample t-test. The result of this research was ten days before and ten days after dividends announcement showed negative market reaction and wasn`t the differenced abnormal return significantly between the company which shares dividend up and the company which shares dividend down. Based on the paired sample t-test result wasÂ  (Î± = 0.05) as significant. It means that negative abnormal return showed that increased dividends shares didn`t have distinct meaning to the information which descreased dividends shares. It indeceted that market wasn`t the information of increasing dividends announcement as references to make investment decision.Â Key words: Abnormal Return, Market Adjust Model dan Event Study.